TRANSFORMASI PEMBELAJARAN BERBASIS DEEP LEARNING: MENINGKATKAN KETERAMPILAN DIGITAL ERA 4.0 BAGI GURU DAN ORANG TUA DI TK KARTINI - Azlin Atika Putri; Sean Marta Efastri; Siti Fadillah; Yesi Novitasari; Ade Tursina (Jurnal ABDI PAUD, 2026)
ABSTRACT This community service activity aims to improve teachers' and parents' understanding of deep learning-based learning transformation and digital skills in the 4.0 era at Kartini Kindergarten, Limapuluh District, Pekanbaru City. The main problems found among partners were a low understanding of deep learning-based learning, minimal digital skills of educators and parents, and the suboptimal use of technology in the early childhood learning process. The activity implementation method was carried out through the stages of planning, socialization, training, practice using digital media, mentoring, monitoring, and evaluation. The activity participated in 30 people consisting of teachers and parents of early childhood. Data collection techniques were carried out through observation, documentation, interviews, and the administration of pre- and post-tests. The results of the activity showed an increase in participants' understanding after participating in the training. The average score of participants' pre-test was 58.3, increasing to 86.7 in the post-test. This increase indicates that the deep learning-based learning transformation training was able to improve the digital skills of teachers and parents in supporting the early childhood learning process. In addition, participants also showed high enthusiasm in practicing the use of digital learning media that is educational and safe for children. This activity has a positive impact on improving the digital competence of teachers and parents as an effort to face the challenges of education in the era of the industrial revolution 4.0.